Youth Perspectives on Dayak Desa Language in Sintang: Challenges and Opportunities for Preservation - Elisa, Henry; Sijono, Sijono; Itu Meo, Ferdinanda (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Research on the use of Dayak Village language in Sintang Regency, especially among young Dayak people, is motivated by the sentiment about the shift in language use and the decreasing number of speakers of the language. The purpose of this study is to see how the position of language use in the social interaction of young Dayak people. This research used a mixed methods approach combining qualitative and quantitative methods, data was collected by surveys and interviews. The participants in this study were students of STKIP Persada Khatulistiwa Sintang aged 17-25 years old. The research findings show that the use of Dayak Village language is in a position that is due to a tendency to decrease the ability, frequency, and scope of its use. This is influenced by social, educational, and psychological factors. The psychological factors that shape the younger generation's attitude towards the Dayak Village language are a strong sense of cultural pride and ownership, which fosters a positive attitude towards preservation. However, some of them experience hesitation or embarrassment in using the language in public due to lack of confidence or fear of judgment. In addition, family is also very important in preserving the Dayak Desa language. Language use by parents significantly affects fluency, while mixed language background or preference towards Indonesian can weaken the use of Dayak Desa. Based on the findings in this study, the following are some recommendations that can be implemented immediately to maintain and develop the Dayak Desa language. Develop technology-based media or teaching materials for Dayak Village language. Integrating Dayak Village language into the school curriculum. Organize Dayak Desa cultural and language events. Increase language opportunities in public spaces and government support for language revitalization.